Relationship Between Basic Life Support Knowledge Level And Basic Life Support Work Skills For Medical Support - Sari, Novita Permata; Mustikowati, Tri; Zuriati, Zuriati (Universitas Muhammadiyah Lamongan, 2022)
Introduction: Knowledge of BLS is necessary not only for medical staff but also for medical support employees because cardiac arrest can occur anytime and anywhere. However, the knowledge and skills of non-medical staff are still under research. This study was conducted to determine the relationship between knowledge and basic life support skills in medical support employees. Methods: This study used a descriptive method with a cross sectional approach. The Chi Square test was used in bivariate analysis to analyze the relationship between knowledge and skills in performing BLS among medical support employees. The study respondents were medical support employees who had worked for 1 year, both those who had attended basic life support training and those who had never attended basic life support training as many as 85 respondents.Results: The findings showed that there was a significant association between BLS knowledge and skills among medical support employees (p < 0.009).Conclusion: Knowledge is an important factor in promoting skills particularly in BLS. Therefore, the development of knowledge about BLS is necessary not only for medical staff but also for medical support employees in order to promote human life in case of cardiac arrest.Keywords: Basic Life Support, Knowledge, Skill